The relationship of stalking behaviours to autism spectrum disorders and personality - Linenberg, Omer (2021)
Stalking perpetration represents a challenge in current forensic research practice in terms of identifying perpetrators and formulating their difficulties, and in developing effective treatment. This thesis explores Autism Spectrum Disorders and Pathological Demand Avoidance (a behavioural profile associated with Autism Spectrum Disorders, characterised by extreme methods of avoiding demands, an anxiety-based need for control over the immediate environment, and turbulent interpersonal relationships) and personality trait models in relation to stalking perpetration. A systematic review identifies the most prevalent clinical factors in stalking perpetration – psychotic disorders and personality disorders. A methodology chapter explores the validity and reliability of online surveys, with emphasis on understanding what makes them suitable for forensic research in the general population, and where the pitfalls may lie. An empirical study investigates the relationship of Pathological Demand Avoidance and Autism Spectrum Disorders with stalking perpetration and personality traits. Pathological Demand Avoidance traits predicted stalking perpetration and Autism Spectrum Disorders traits did not; a mediation analysis exploring the hypothesis that Pathological Demand Avoidance predicted stalking perpetration by way of strategic emotional control was non-significant, suggesting this was not related to stalking perpetration. The relationship of the HEXACO personality traits model to Pathological Demand Avoidance and stalking perpetration was examined, finding that higher levels of Emotionality and lower levels of Honesty predicted stalking perpetration independently of Pathological Demand Avoidance A second post-hoc study found that the gender distribution in the sample overall did not impact the relationships found between Pathological Demand Avoidance, Autism Spectrum Disorders, and stalking perpetration. Females in general scored more highly than males on the Emotionality and Extraversion aspects of the HEXACO model, and a Chi-square analysis indicated no significant differences between genders on specific types of stalking behaviours perpetrated.